Polypharmacy and Probable Drug Interactions in Cardiovascular Patients at a Tertiary Care Hospital - Shetty, Srajana; Paladi, Rakshita; Basavaraj, Sachin; Nyamagoud, Sanatkumar Bharamu; Swamy, Agadi Hiremath Vishwanath; Goudar, Latha Maregouda; Bhupathiraju, Sai Sowmya; Khandke, Shruti Achyut; Walvekar, Arpita Ravindra; Salgare, Shreya; Sirdesai, Nida Khanum (International Journal of Pharmaceutical Investigation, 2026)
Background Cardiovascular Disease (CVD) is a general term for conditions affecting the heart or blood vessels. Globally, CVDs are the primary cause of morbidity and mortality. Frequently, treating CVDs requires intricate and comprehensive treatment plans. Heart disease and stroke are predicted to overtake all other causes of mortality and disability globally by 2020. Polypharmacy, the use of multiple medications, is prevalent among CVD patients, managing risk factors and comorbid conditions. However, it raises the risk of adverse drug interactions, necessitating Drug-Drug Interaction (DDI) monitoring to reduce negative medication responses. Objectives We aimed to assess the prevalence of polypharmacy in cardiovascular disease patients. Materials and methods: 170 participants participated in a six-month cross-sectional study conducted at the cardiology department Patients with two or more prescription drugs and a minimum age of 18 were included in the research. A Micromedex drug interaction checker was used to identify and analyze the pattern of probable DDIs. Results The study found that 132 (77.6%) of patients with CVD use 5 to 9 medicines due to multiple disorders. Factors like age, gender, and comorbidities significantly impact polypharmacy, with aspirin and clopidogrel being the most common drug interaction, causing major interactions whereas atorvastatin and clopidogrel cause moderate interaction. Conclusion The study concluded that a high prevalence of polypharmacy in hospitalized cardiac patients is influenced by factors like age, gender, and comorbidities. DDI’s were common, with Aspirin and Clopidogrel showing high rates of major interactions while atorvastatin and clopidogrel showed moderate interaction. It emphasizes the need for careful medication management to avoid harmful interactions.
Keywords: CVD; DDI; Polypharmacy Aspirin; Clopidogrel